UPAYA MENINGKATKAN KESADARAN MASYARAKAT TENTANG PENTINGNYA KEBERSIHAN KESEHATAN LINGKUNGAN - Dewi, Fatqu Rofiqoh; Dewi, Novi Rina (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2025)
Environmental cleanliness is the key to maintaining the quality of life and public health. Thus, environmental cleanliness is very important. This article emphasizes the importance of maintaining environmental cleanliness to protect public health and the negative impacts of a dirty environment. Therefore, we will discuss environmental issues such as the lack of public awareness about environmental cleanliness, particularly around residential areas and some places of worship. In addition, this article also educates the public to create a clean and healthy environment. This article analyzes various factors that influence community behavior in waste disposal, which is one of the important factors in maintaining environmental cleanliness. These factors include environmental awareness, the availability of facilities, and the enforcement of regulations. The development of technology has provided many innovative solutions in waste management. This article discusses several of the latest technologies that can be used to process waste, such as recycling, composting, and waste-to-energy. In addition, this article will also discuss the challenges and opportunities in the implementation of these technologies in Indonesia.